Overall survival and mortality risk factors in Takayasu's arteritis: A multicenter study of 318 patients. (January 2019) - Mirouse, Adrien; Biard, Lucie; Comarmond, Cloé; Lambert, Marc; Mekinian, Arsène; Ferfar, Yasmina; Kahn, Jean-Emmanuel; Benhamou, Ygal; Chiche, Laurent; Koskas, Fabien; Cluzel, Philippe; Hachulla, Eric; et al.
Abstract: Objective: To report the long term mortality in Takayasu arteritis (TA) and to identify prognosis factors. Methods: We analyzed the causes of death and the factors associated with mortality in a cohort of 318 patients [median age at diagnosis was 36 [25–47] years and 276 (86%) patients were women] fulfilling American College of Rheumatology and/or Ishikawa criteria of TA. A prognostic score for death and vascular complications was elaborated based on a multivariate model. Results: Among 318 TA patients, 16 (5%) died after a median [IQR] follow-up of 6.1 [2.8–13.0] years. The median age at death was 38 [25–47] years with 88% of women. Main causes of death included mesenteric ischemia (n = 4, 25%) and aortic aneurysm rupture (n = 4, 25%). The mortality rate at 5 and 10 years was of 1.9% and 3.9%, respectively. Caucasians (p = 0.049) and smokers (p = 0.002) TA patients were more likely to die. There was an increased mortality in TA (SMR with 95% confidence interval, 2.73 [1.69–4.22]) as compared to age and sex matched healthy controls. We defined high risk patients for death and vascular complications according to the presence of two of the following factors ( i.e a progressive clinical course, thoracic aorta involvement and/or retinopathy). In the high risk TA group, the 5-year incidence of death and vascular complication was 48.5% compared to 21.6% (p = 0.001) in those with low risk. Conclusion: The overall mortality in our Takayasu cohort was 5% after a median follow-up of 6.1 years. We identified specific characteristics that distinguish TA patients at highest risk for death and vascular complications. Highlights: We report the long term mortality in a cohort of 318 patients with Takayasu arteritis. We report an overall mortality of 5% after a median follow-up of 6.1 [2.8–13.0] years. Patients with TA had a standardized mortality ratio (SMR) of 2.7 [CI 95% 1.69–4.22]. We developed a prognosis score that allow classifying patients as low or high risk to death or vascular complication. The prognosis score is based on disease course pattern, thoracic aorta involvement, and retinopathy.